INFORMATION SYSTEM DESIGN OF VILLAGE-OWNED ENTERPRISES IN PEKON SINAR PETIR, BASED ON WEB AS A PROMOTIONONAL MEDIA FOR VILLAGE SUPERIOR PRODUCTS - Sri Ipnuwati; Sri Surya Mandala; Dimas Irianto Ardi (Bakti Nusantara Institute, 2023)
The development of this era in the field of information technology is very fast. This phenomenon will certainly change and become a tool for business competition between companies and organizations. A village-owned enterprise is a business entity formed based on Law No. 6 of 2014 concerning villages. With the formation of village-owned enterprises, it is hoped that villages will become independent and be able to improve the economic level of the community. In this case, the village-owned enterprise